2005
DOI: 10.1002/neu.20087
|View full text |Cite
|
Sign up to set email alerts
|

Neural song preference during vocal learning in the zebra finch depends on age and state

Abstract: The zebra finch acquires its song by first memorizing a model song from a tutor and then matching its own vocalizations to the memory trace of the tutor song, called a template. Neural mechanisms underlying this process require a link between the neural memory trace and the premotor song circuitry, which drives singing. We now report that a premotor song nucleus responds more to the tutor song model than to every other stimulus examined, including the bird's own song (BOS). Neural tuning to the song model occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
91
2

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 88 publications
(104 citation statements)
references
References 37 publications
11
91
2
Order By: Relevance
“…Bolhuis & Gahr (2006) suggested that during song learning there is continual interaction between regions in the auditory forebrain and the song system. Electrophysiological analyses have shown that during the first half of the sensorimotor phase (35-69 dph), neurons in the HVC of male zebra finches respond preferentially to the tutor song, whereas during the second half of the sensorimotor phase, and in adult zebra finches and whitecrowned sparrows, there is preferential responding to the BOS (Volman 1993;Nick & Konishi 2005). Recently, it was found that lesions to the HVC in zebra finch males in the early sensorimotor phase (33-44 dph) did not impair the production of subsong (Aronov et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Bolhuis & Gahr (2006) suggested that during song learning there is continual interaction between regions in the auditory forebrain and the song system. Electrophysiological analyses have shown that during the first half of the sensorimotor phase (35-69 dph), neurons in the HVC of male zebra finches respond preferentially to the tutor song, whereas during the second half of the sensorimotor phase, and in adult zebra finches and whitecrowned sparrows, there is preferential responding to the BOS (Volman 1993;Nick & Konishi 2005). Recently, it was found that lesions to the HVC in zebra finch males in the early sensorimotor phase (33-44 dph) did not impair the production of subsong (Aronov et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The neural song system is a series of anatomically distinct clusters of neurons (nuclei) in the thalamus, basal ganglia, and pallium (cortex) that are dedicated to the production and plasticity of song (Bottjer et al 1984;Nottebohm et al 1976). The nucleus HVC (Reiner et al 2004) is a pallial brain region that controls song behavior (Nottebohm et al 1976;Vu et al 1994).…”
Section: Introductionmentioning
confidence: 99%
“…The nucleus HVC (Reiner et al 2004) is a pallial brain region that controls song behavior (Nottebohm et al 1976;Vu et al 1994). During anesthesia (Volman 1993) and sleep (Nick and Konishi 2005a), HVC always responds preferentially to the bird's own song, even very early in song development.…”
Section: Introductionmentioning
confidence: 99%
“…One possibility is that feedback signals are gated in a highly dynamic fashion as a function of behavioural and/or developmental state. In fact, HVC neurons in juvenile zebra finches appear to respond more readily to auditory stimulation during periods of quiet wakefulness than do HVC neurons in adults [61,103]. However, whether this developmental difference in responsiveness extends to feedback is unclear, and recordings made in the HVC of juvenile zebra finches have failed to detect changes in singing-related action potential activity in response to acute feedback perturbations [37].…”
Section: Developmental Origins Of Auditory -Vocal Mirroringmentioning
confidence: 99%